A Review on the Unpacking of Online learning Self-Efficacy Article by Shen, Cho, Tsai, & Marra (2013) - Ibsahrodan, Ervan (Universitas Lancang Kuning, 2020)
The discourse of traditional versus online learning is not made distinct by the technological aspect only, but also the levels of students’ self-efficacy. Self-efficacy is the ability to control and manage one’s motivations, behaviour, and social environment in order to continue and consistently complete any tasks. This study aims to understand the discourse of online learning self-efficacy by reviewing a selected article due to its considerable influence in this specific body of work to this date. Using content analysis in a qualitative design, this study reviewed Shen, Cho, Chai, & Marra’s (2013) article entitled “Unpacking online learning experiences: Online learning self-efficacy and learning satisfaction.” The results of this article are the comprehensive discussion of the article’s strengths and weaknesses and the article’s general context with the IMRAD framework.